External instability in transition: Applying Minsky's theory of financial fragility to international markets - Liudmila Malyshava (Levy Economics Institute of Bard College, 2018)
This inquiry argues that the successful completion of the transition process in the post-Soviet economies is constrained by the prevailing social structure and low levels of technological progress, both of which require institutional reforms aimed at increasing growth in national income, productivity, and the degree of export competitiveness. Domestic policy implementation has not shown significant improvements on these fronts, given its short-term orientation, but instead resulted in stagnating growth rates, continuously accumulating levels of external debt, and decreasing living standards. The key to a successful completion of the transition process is therefore a combination of policies targeted at the dynamic transformation of production structures within an environment of financial stability and favorable macroeconomic conditions.
Keywords: B25; F13; F34; G15; P30; 330; Transition Economies; Soviet Mode of Production; Technological Decay; International Capital Flows; External Instability; Debt Repayment